Combination treatment for hypertension - J. Ker (South African Family Practice)
On average, one in four adults has hypertension.1 This figure is higher in certain regions of the world, and in certain areas within countries. Worldwide, however, the prevalence of hypertension is on the rise. The relationship between level of blood pressure and risk for cardiovascular events is linear and continuous. Nearly 75% of adults with other cardiovascular disease have hypertension as a comorbidity. Hypertension is associated with shorter overall life expectancy, as well as a shorter life expectancy free of cardiovascular disease. Hypertension can be said to be controlled or at goal if blood pressure is less than 140/90 mmHg, or less than 130/80 mmHg for those with diabetes, kidney disease or a previous vascular event (e.g. myocardial infarction, stroke, etc).